2001
DOI: 10.4049/jimmunol.166.12.7014
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: IL-18-Transgenic Mice: In Vivo Evidence of a Broad Role for IL-18 in Modulating Immune Function

Abstract: IL-18 has been shown to be a strong cofactor for Th1 T cell development. However, we previously demonstrated that when IL-18 was combined with IL-2, there was a synergistic induction of a Th2 cytokine, IL-13, in both T and NK cells. More recently, we and other groups have reported that IL-18 can potentially induce IgE, IgG1, and Th2 cytokine production in murine experimental models. Here, we report on the generation of IL-18-transgenic (Tg) mice in which mature mouse IL-18 cDNA was expressed. CD8+CD44high T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
79
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 24 publications
9
79
1
Order By: Relevance
“…Interestingly, IL-18 has also a role in the Th2 immune response since it enhances IL-13 production by T and NK cells when combined with IL-2 [42] and induces the secretion of IL-4, IL-5 and IL-10 in vivo in mouse models of disease [43][44][45]. Consistent with these observations IL-18 transgenic mice have been shown to produce high levels of both Th1 and Th2 cytokines [46]. A c c e p t e d M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 10…”
Section: Interleukin-18supporting
confidence: 63%
“…Interestingly, IL-18 has also a role in the Th2 immune response since it enhances IL-13 production by T and NK cells when combined with IL-2 [42] and induces the secretion of IL-4, IL-5 and IL-10 in vivo in mouse models of disease [43][44][45]. Consistent with these observations IL-18 transgenic mice have been shown to produce high levels of both Th1 and Th2 cytokines [46]. A c c e p t e d M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 10…”
Section: Interleukin-18supporting
confidence: 63%
“…It has been previously demonstrated that IL-18 induces the production of both Th1-and Th2-type cytokines, including IL-13, -4 and IFN-c, both in vitro and in vivo [16][17][18]. Very recently, the present authors established lung-specific IL-18 Tg mice that constitutively overproduce IL-18 in their lungs.…”
Section: Discussionmentioning
confidence: 94%
“…It has been reported that low levels of pro-and mature IL-18 proteins are expressed in the lungs of healthy subjects [15]. HOSHINO and co-workers [16][17][18] have shown that IL-18 can act as a co-factor for both Th1 and Th2 cell development, and several studies have subsequently reported that IL-18 may be involved in the development of Th2-type-diseases, such as asthma [14]. The present authors have previously demonstrated that treatment with recombinant IL-18 plus IL-2 induces pulmonary inflammation and lung injury in mice [19], and IL-18 and its receptor are strongly expressed in the human lung in idiopathic pulmonary fibrosis [15].…”
mentioning
confidence: 99%
“…Furthermore, when IL-18 was combined with IL-2, there was a synergistic induction of IL-13 in both T and NK cells [17]. IL-18 can also induce IgE, IgG1 and Th2 cytokine production in murine experimental models [19,20], and IL-18 transgenic mice produce higher levels of IL-4, IL-5, IL-13 and IFN-c [21]. Taken together these studies indicate that IL-18 is a pleiotropic cytokine that may under some circumstances augment type 2 as well as type 1 immunity.…”
Section: Introductionmentioning
confidence: 99%